POLA KONSUMSI ZAT GIZI MAKRO DAN AKTIVITAS FISIK ANAK USIA 13-15 TAHUN - Afandi, Muhammad Khoiron; Avandi, Raymond Ivano (Journal of Sport and Exercise Science, 2022)
In their daily life, player at the age of teenagers have unhealthy lifestyles such as lack of intake of macronutrients which consist of carbohydrates, fast and protein which are not balanced with physical activity, if not balanced it will lead to problems in nutrition, every player has nutritional consumption and different activities differences that create dissimilarities between players, as well as a lack of knowledge to start the process of maturity or change. The purpose of this study was to determine the consumption pattern of macronutrients and physical activity in player who took part in futsal extracurricular activities at SMP Negeri 5 Sidoarjo. Using a descriptive method of 2 variables with a quantitative approach, members of the study with a sample of 30 students. The technique of collecting data is by using a porposive sampling method or a method of collecting data with certain considerations. How to analyze the sample using the Physical Activity Questionnare-Adolescents (PAQ-A) and 24-hour food recall assisted by the nutrisurvey application, done by pouring frequency into percentage from. From the survey results of 30 samples at most, there were 46,70% deficit energy intake with 14 player, 50,00% excess protein consumption with 15 players, 56,70% normal fat consumption with 17 players, the same 50,00% carbohydrate consumption less and normal. The result of the physical activity analysis showed 70% in the low category with 21 player. With normal consumption pattern of macronutrients, it is necessary to increase them and physical activity with moderate results. Physical activity of a player obtains additional adequate and balanced nutrition, it appears to have a good nutritional consumption pattern.